The green space : the transformation of the Irish image - Casey, Marion R., 1962- (New York University Press, 2024)
"There is more to Irish than St. Patrick's Day and Guinness. The word Irish conjures an array of images, each with a long history. Who defined Irish? In the twentieth century Ireland, the United States, and Irish America were all invested in representation. Exerting or losing control of an ethnic image had ramifications on both sides of the Atlantic"-- Provided by publisher.
Keywords: National characteristics, Irish.; Irish -- Ethnic identity.; Irish Americans -- History.; Ireland -- History -- 20th century.; Irlandais.; Irlandais -- Identité ethnique.; Irlande -- Histoire -- 20e siècle.; HISTORY / United States / General.; Irish Americans.; Ireland.; 1900-1999; History.